Pengaruh Risiko Kerja Dan Upah Minimum Terhadap Produktivitas Kerja - Malakiyyah, Siti Nurhalifah; Tazliqoh, Agustifa Zea (Peneliti.net, 2025)
In the competitive business world, work productivity is an important factor for company success. This research examines how work risks and minimum wages affect work productivity. Using multiple linear regression analysis, this research collected data from 80 employees at Company